Inotropes in Acute Heart Failure: From Guidelines to Practical Use: Therapeutic Options and Clinical Practice - Vasiliki Bistola; Angelos Arfaras-Melainis; Eftihia Polyzogopoulou; Ignatios Ikonomidis; John Parissis (Cardiac Failure Review)
Inotropes are pharmacological agents that are indicated for the treatment of patients presenting with acute heart failure (AHF) with concomitant hypoperfusion due to decreased cardiac output. They are usually administered for a short period during the initial management of AHF until haemodynamic stabilisation and restoration of peripheral perfusion occur. They can be used for longer periods to support patients as a bridge to a more definite treatment, such as transplant of left ventricular assist devices, or as part of a palliative care regimen. The currently available inotropic agents in clinical practice fall into three main categories: beta-agonists, phosphodiesterase III inhibitors and calcium sensitisers. However, due to the well-documented potential for adverse events and their association with increased long-term mortality, physicians should be aware of the indications and dosing strategies suitable for different types of patients. Novel inotropes that use alternative intracellular pathways are under investigation, in an effort to minimise the drawbacks that conventional inotropes exhibit.